Abel Iloco documenting the traditional knowledge of Ilocos region - Campos, Aldrin Joseph P.; Obille, Kathleen Lourdes B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2018)
The Ilocos Region is proud to have the abel Iloco as one of the treasures of the region. Unfortunately, the abel weaving process is slowly being forgotten and the tradition is on the verge of dying. The bakbaket are the elders in the community, they hold different knowledge about culture, history and tradition. These bakbaket hold the knowledge of abel weaving and do the amazing craft by heart. But the elders are ageing, and their number decreased over time and at times the knowledge are not being passed to newer generation. Martin (2009) noted that the continuous passage of intangible cultural heritage from generation to generation is the life support of these objects.
The abel weaving process of Region is at risk of being lost and in danger that the traditional knowledge can never be known by the future generation. That is why this study saw the importance of documenting the traditional abel weaving process of the region. The study aimed to document the traditional weaving and the knowledge that the weavers hold. The abel weavers are located in the weaving communities in Currimao, Sarrat, Pinili, Vigan, Caoayan, Bauang, Aringay, Bangar. The weavers were not formally taught by their mother, aunts and grandmothers but they perfected the craft and added some modern adjustments to the process. Some of the steps of the traditional abel weaving process is still similar from what the weavers are following. The knowledge of weaving is being passed from an expert weaver to its apprentices. Fortunately, the abel weaving communities have passionate weavers who leads the other abel weavers in pursuit of reviving the dying tradition. Through them the continuous flow of knowledge is being passed unto new generations, keeping the tradition alive.
Thesis
Keywords: Intellectual property; Indigenous peoples .; Traditional ecological knowledge; Intangible property; Cultural property -- Protection